Peldēšanas prasmju apguves problēmas un to risinājumu iespējas - Gultniece, Lelde (Latvijas Universitāte, 2009)
Diplomdarbs ir par peldēšanas prasmju apguves problēmām un to risinājumu iespējām. Teorētiskajā daļā ir analizēta literatūra par peldēšanas vēsturi, stilu tehnisko izpildījumu un vietu skolu mācību programmās. Praktiskajā daļā tiek apzināta obligātās peldētapmācības 2. klasēm situācija Rīgas skolās, kā arī skolēnu attieksme pret peldēšanu. Kā risinājumi ir izstrādāts vingrinājumu komplekss sporta stundās peldēšanas prasmju apguvei skolēniem, kuriem nav pieejams peldbaseins, kā arī informatīvais materiāls par peldēšanas pozitīvo ietekmi uz cilvēka veselību. Atslēgvārdi: obligātā apmācība, peldētprasme, peldēšanas vēsture, skola

The diploma work is about main problems in acquiring swimming skills and probable solutions. In the theoretical part the literature about history of swimming, technical skills in performing swimming styles and significance in the school education programmes is analysed and as well as psycho physiological characterization of pupils of respective age. In the practical part of the work the situation in the schools of Riga in obligatory training course of swimming for pupils of the 2nd class of the primary school is studied and as well as pupils’ attitude to swimming. Complex drills for swimming lessons in order to teach swimming skills to pupils who does not have access to a swimming pool has been developed as a solution as well as an informative material about positive effect of swimming on the health of a human. Keywords: compulsory education, swimming skills, history of swimming, school.
Problems of acquisition swimming ability and of its solving facility.
Keywords: Pedagoģija